Faktor Risiko Kejadian Sick Building Syndrome Pada Pegawai Dinas Lingkungan Hidup Dan Kehutanan Provinsi Jawa Tengah - Alfadhylla Rosalina Wibisono; Nurjazuli Nurjazuli; Tri Joko; Suhartono Suhartono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Based on initial observations, 60% of the employees of the Environment and Forestry Office of Central Java Province experienced symptoms of Sick Building Syndrome (SBS). The purpose of this study was to identify the symptoms of SBS and individual characteristics (age, sex, years of service, and smoking habits), measure the physical environmental air quality (temperature, humidity, lighting, and ACH), and also analyze the individual characteristics and physical environmental air quality with the occurance of SBS. This study used an analytic observational study design with a cross-sectional study approach. The number of samples in this study was 28. Data analysis includes univariate, bivariate and statistical tests using chi-square. The results showed that 60.7% of employees experienced SBS (17 people) and 39.3% of respondents did not experience SBS (11 people). There was no relationship between temperature (p value = 0.688), humidity (p value = 0.396), age (p value = 0.937), and years of service (p value = 0.159) with the incidence of SBS. Meanwhile, gender (p value = 0.038) and smoking habits (p value = 0.001) were associated with the incidence of SBS. SBS symptoms are felt in the form of dry skin, nosebleeds, sneezing, itching, and itchy eyes. The conclusion of this study is that there is a relationship between gender and smoking habits with the incidence of SBS, and there is a relationship between sex and smoking habits with the incidence of SBS in employees of the Environment and Forestry Service of Central Java Province.